The Framework for the Supplier Qualification System for the World Leader Home Appliances Industry - Joanna Graczyk-Tarasiuk; Kanisius Karyono; Kanisius Karyono (Technologia i Automatyzacja Montażu)
The aim of this study is to analyze and evaluate the supplier qualification system used in production plants of the world leader in the household appliances industry and to present proposals for improvement actions. The concern uses the "20 Steps Procedure", which is a set of guidelines for each stage of qualifying suppliers of components for production processes. It systematizes individual activities and sets the powers and responsibilities of the departments involved in various phases of the qualification process. This article describes its three phases. An important element of the procedure is a detailed supplier auditing system. It is necessary to be sure that a supplier has an effective management system and controls its production processes, and that the manufactured elements meet all the concern's requirements. The presented system of supplier evaluation and qualification seems to indicate a rather cautious approach of the concern to the admission of new suppliers of components or semi-finished products. Criteria used in this area are very critical, but formulated in a very clear and transparent manner, understandable both for the company's auditors and for current and future suppliers.